Polydioxanone suture fixation for the repair of pediatric maxillofacial fractures (Annals of Medical Research, 2021)
Aim: Unique pattern of the pediatric facial skeleton and its fractures confers a special issue to take into account. Conservative management, occlusal splints and wiring techniques are popular among pediatric facial fractures. As titanium plates require plate removal after the fracture healing, resorbable plates have gained popularity. However, they are expensive and it may not be possible to obtain resorbable plates in some medical facilities. This led us to question the mechanical stability and functional outcome after fracture fixation using polydioxanone (PDS) sutures.Material and Methods: Seven children with maxillofacial fractures were included in this study. After limited sufficient dissection and periosteal striping the fracture lines were reduced and four holes were made with a drill on preoperatively planned sites where no tooth buds were projected. After that a number 2 PDS loop suture was passed through these holes in a figure of eight fashion and tied to stitches after sufficient stability and anatomic reduction.Results: No complication occurred, except for two cases that had tooth extractions.Conclusion: To sum up, PDS suture fixation in a figure of eight fashion is a feasible and cheap alternative to titanium and resorbable plate systems.